THE ECOCRACY OF WATER RESOURCES ON WATER CULTIVATION RIGHTS IN REALIZING SOIL AND WATER CONSERVATION - Setia Untung Arimuladi (Jurnal Pembaharuan Hukum, 2022)
There are still several problems related to water resources, which can affect poverty, food shortages, hamper economic growth, and disrupt ecosystems. Based on the literature study, two conclusions were generated. First, the function of Water Resources in business activities in laws and regulations still ignores the constitutional rights of the state and the people through the gap for companies to manage and make water and water resources as the profit-oriented business. Second, it is necessary to revitalize ecocracy in ensuring the existence of Water and Soil Conservation by inculcating two (legal) liabilities, namely the liability due to the inherent propriety to act or to do and the liability due to the inherent propriety not to act or not to do to protect ecosystem health and to ensure the environmental sustainability. It is necessary to reform the Water Resources Law in tackling the exploitation of water resources to justify monopoly or illegal profits made by certain parties.